Historical management of equine resources in France from the Iron Age to the Modern Period. (December 2021) - Lepetz, Sébastien; Clavel, Benoît; Alioğlu, Duha; Chauvey, Lorelei; Schiavinato, Stéphanie; Tonasso-Calvière, Laure; Liu, Xuexue; Fages, Antoine; Khan, Naveed; Seguin-Orlando, Andaine; Der Sarkissian, Clio; Clavel, Pierre; et al.
Highlights: The Horse is the only equid species identified in the Iron Age archaeological record from France. Mules represent an abundant fraction of the equine bone assemblages from France during the Roman Period, while donkeys were almost absent. Donkeys of exceptional size were present in France during the Late Antiquity. Following the collapse of the Roman Empire, donkeys replaced mules and became an important element of economic activities. Abstract: Alongside horses, donkeys and their first-generation hybrids represent members of the Equidae family known for their social, economic and symbolic importance in protohistoric and historical France. However, their relative importance and their respective roles in different regions and time periods are difficult to assess based on textual, iconographic and archaeological evidence. This is both due to incomplete, partial and scattered historical sources and difficulties to accurately assign fragmentary archaeological remains at the proper taxonomic level. DNA-based methods, however, allow for a robust identification of the taxonomic status of ancient equine osseous material from minimal sequence data. Here, we leveraged shallow ancient DNA sequencing and the dedicated Zonkey computational pipeline to obtain the first baseline distribution for horses, mules and donkeys in France from the Iron Age to the Modern period. Our collection includes a total of 873 ancient specimens spanning 128 sites and comprising 717 horses, 100 donkeys, 55 mules and a single hinny individual. While horses were ubiquitous and the most dominant species identified, our dataset reveals the importance of mule breeding during Roman times, especially between the 1st and 3rd centuries CE (Common Era), where they represented between 20.0% and 34.2% of equine assemblages. In contrast, donkeys were almost absent from northern France assemblages during the whole Roman period, but replaced mules in rural and urban commercial and economic centers from the early Middle Ages. Our work also identified donkeys of exceptional size during Late Antiquity, which calls for a deep reassessment of the true morphological space of past equine species. This study confirmed the general preference toward horses throughout all time periods investigated but revealed dynamic management strategies leveraging the whole breadth of equine resources in various social, geographic and temporal contexts.